Estrés y rendimiento académico en adolescentes entre 14 a 18 años de la Unidad Educativa Francisco Huerta Rendón de la Ciudad de Babahoyo - Di Lorenzo Sanchez, Mirian Abigail (2024)
This research explores the relationship between academic stress and academic performance in 14-18 year-old students at the Francisco Huerta Rendón Educational Unit, exploring how educational pressures affect adolescents' academic ability. Using a mixed methodological design, different dimensions of academic stress are examined, including its causes, manifestations, and impact on students' learning and performance. Findings indicate a significant correlation between high levels of academic stress and low academic outcomes, highlighting the importance of effective stress management strategies to improve educational performance. Through a detailed analysis, this study proposes recommendations for the implementation of psychoeducational support programmes that foster a healthier and more productive learning environment. Thus, it emphasises the need for comprehensive approaches that include the participation of educators, parents and the education system as a whole, in order to mitigate the impact of stress in the academic environment.